Searching for Lord Haw-Haw : the political lives of William Joyce - Holmes, Colin (Routledge studies in fascism and the far right, 2016)
"Searching for Lord Haw-Haw is an authoritative account of the political lives of William Joyce. He became notorious as a fascist, an anti-Semite and then as a Second World War traitor when, assuming the persona of Lord Haw-Haw, he acted as a radio propagandist for the Nazis. It is an endlessly compelling story of simmering hope, intense frustration, renewed anticipation and ultimately catastrophic failure. This fully-referenced work is the first attempt to place Joyce at the centre of the turbulent, traumatic and influential events through which he lived. It challenges existing biographies, which have reflected not only Joyce's frequent calculated deceptions but also the suspect claims advanced by his family, friends and apologists. By exploring his rampant, increasingly influential narcissism it also offers a pioneering analysis of Joyce's personality and exposes its dangerous, destructive consequences. 'What a saga my life would make!' Joyce wrote from prison just before his execution. Few would disagree with him"--